Analyzing Student Mobility Patterns and Route Preferences: A GIS- and Mental Map-based Study at Politeknik Negeri Ujung Pandang, Indonesia - Ridwan, Vita Fajriani; Matsumura, Nobuhiko; Sarif, Sarif; Zakariah, Aisyah; Anton, Erning Ertami (Institute of Research and Community Outreach - Petra Christian University, 2026)
Current understanding of students’ mobility patterns often overlooks the integration of perceptual experiences with spatial behavior, particularly in rapidly urbanizing Global South contexts where informal infrastructures and cognitive factors critically shape mobility. This study addresses this gap by analyzing route preference determinants at Politeknik Negeri Ujung Pandang using mental map sketches (n=165), questionnaires, and GIS-based spatial analysis. Key findings reveal: 1) dense morning commutes within 500m of campus versus afternoon dispersal into alternative routes up to 2km; 2) distance (r = 0.876, p < 0.01) and travel time (r = 0.699, p < 0.01) dominate choices, outweighing convenience (r = 0.196, p < 0.05); and 3) gendered behaviors, with 65% of alternative route users were males. The findings validate Hägerstrand’s Time-Geography model and recommend arterial corridor optimization and safety retrofits, advancing an equitable framework for campus mobility planning.